Superman: entre quadrinhos, discurso e ideologia. - Silva, Marcelo Travassos da (2019)
The first comic book superhero is the result of a crisis of American society after the fall of the New York Stock Exchange in 1929. Recognizing comic-book narratives as a segment of modern journalism, known as ninth art and which has great acceptance of the masses, this work aims to discuss and reflect the discursive construction of the fictional character Superman, through ten selected narratives. Written and drawn by two Jewish teenagers, Jerry Siegel and Joe Shuster, the visual text of the Steel Man came to fill a United States lack for a hero a good example to help the American people overcome a period of many problems, similar with the Brazilian crisis after 2014. Through the critical analysis of the discourse, based on the text of Norman Fairclough, this work analyzes comic book stories published between 1938 and 2003. Each of these visual texts is presented, divided into sequences, tables static and analyzed in the perspective of linguistics, also highlighting elements of semiotics. Recognizing the three-dimensional model of Fairclough and discussing the text, discursive practice and social practice of Steel Man is important for a better understanding of reality, just as it is also possible to perceive the relation between fiction and social reality, from gender not always valued. Within this, this research presents as a result a new reading and interpretation of the first superhero of the world, recognizing it as a character that is part of an American hegemonic strategy of ideological domination that uses play texts to transmit messages not produced by the superhero , but by the other. Thus, Kryptonian fiction is important for reproducing discourses that serve interests that are part of social reality.